The Relationship between Posyandu Cadre Knowledge Level with Anthropometric Measurements and Filling in Child Development Card (KKA) - Wa Fonika; Islami Islami; Septiani Septiani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anthropometric measurements and completing the Child development cardat integrated health posts (Posyandu) are essential components of monitoring toddler growth and development. In the Fakfak Tengah Community Health Center (Puskesmas) work area, measurement coverage only reached 47.13%, and most KKA completions were still carried out by nutrition workers, with errors being found among the cadres. This situation indicates the need to improve cadre capacity. This study aimed to analyze the relationship between Posyandu cadres' knowledge level and their skills in anthropometric measurement and KKA completion. The study used a quantitative, observational design with a cross-sectional approach. A sample of 76 cadres was purposively selected from 19 Posyandus in the Fakfak Tengah Community Health Center work area from July to August 2025. The independent variable was the cadres' knowledge level regarding Posyandu services, while the dependent variables were their skills in anthropometric measurement and KKA completion. The research instruments consisted of a knowledge questionnaire and a skills observation sheet. Data analysis was performed using univariate analysis to describe respondent characteristics, and bivariate analysis using the Chi-square test to test relationships between variables at a 95% significance level (p<0.05). The results showed that Posyandu cadre knowledge was associated with anthropometric measurements (OR = 3.26; 95% CI: 1.11–9.57; p = 0.028), and completion of the Child development card (7.17 (95% CI: 1.41–36.50); p = 0.014). Posyandu cadre knowledge was associated with anthropometric measurements and completion of the child development card.